Nature Therapy pada Komunitas Mahasiswa Pecinta Alam - Cahaya D. Silitonga; Latifa Haliza Noermartanto; Ummi Nur Al Rohmah; Muslikah Muslikah; Ashari Mahfud (Lembag, 2024)
One of the communities most often looked at or interested by students is the student community of nature lovers. This community offers in-depth knowledge about interesting activities that can be done in nature, so it can be a place for students who have more interest in nature. There are many reasons why they have an interest in doing activities in nature, including hobbies, fomo, and the most common reason is because they want to overcome stress. According to them, activities in nature such as hiking, trekking, and diving can be a therapy when they are experiencing problems. In addition, nature provides positive energy that makes the brain fresh. The purpose of this study is to discuss the benefits of nature as therapy for the student community of nature lovers. In this study we used a qualitative approach with a focus on phenomenology, data collection techniques were carried out using in-depth interview methods. This research is expected to provide an overview of activities in nature that can be used as therapy to overcome stress, add relationships and alternative vacations.